"I don't want trouble": Freedom of expression and use of backchannels in the wake of Typhoon Haiyan. Issue 4 (5th June 2018) - Longboan, Liezel
Abstract : Purpose: Studies which look at disaster affected people's use of communications technologies often fail to take into account people's communication rights in their analyses, particularly their right to freedom of expression. The purpose of this paper is to draw attention to this issue by exploring the link between freedom of expression, community participation and disaster risk reduction in the use of digital feedback channels offered by aid and government agencies in the aftermath of Typhoon Haiyan. Design/methodology/approach: Ethnographic fieldwork was undertaken in the Philippines between 2014 and 2015 in Tacloban City and Sabay Island, both in the Visayas, which have been affected by Typhoon Haiyan. A total of 101 in-depth interviews were conducted with affected people, local and national officials, community leaders, civil society groups, telecommunications companies and humanitarian agencies. Findings: The interviews reveal that majority of disaster-affected Filipinos chose not to engage with formal feedback platforms offered by government and aid agencies out of fear of giving critical feedback to those in authority. They were concerned about the possibility of losing their entitlement to aid, of being reprimanded by government officers, and of the threat to their lives and of their loved ones if they expressed criticism to the government's recovery efforts. Nonetheless, 15 per cent used backchannels while 10 per cent availed of the formal means to express their views about the recovery. Research limitations/implications: The paper sought to draw links between people's lack of engagement with the formal feedback mechanisms offered by government and aid agencies in the wake of Haiyan and the restrictive sociopolitical environment in the Philippines. Further research could be undertaken to examine how freedom of expression plays a role in disaster prevention and mitigation. Research into this area could potentially provide concrete steps to help prevent the occurrence of disasters and mitigate their impacts. Originality/value: Freedom of expression and its place in disaster risk reduction is rarely explored in disaster studies. The paper addresses this oversight by examining the lack of engagement by communities affected by Haiyan with digital feedback channels provided by aid agencies and government. The findings suggest that despite the provisions for community participation in DRR under the Philippine Disaster Law, people are prevented to express criticism and dissent which puts into question the spirit and purpose of the law.